English Language Anxiety and Motivation towards Speaking English among Thai Tertiary Students - Thomol, Piyanut; Tutwisoot, Worawoot; Klanrit, Prayong (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2024)
This study aimed to address challenges faced by students in speaking English effectively. The objectives were: 1) to investigate the levels of motivation for speaking English among students in the Faculty of Education at Udon Thani Rajabhat University; 2) to examine the levels of anxiety associated with speaking English among these students; and 3) to explore the relationship between motivation and anxiety in English-speaking skills. A total of 411 students, selected through stratified random sampling from a population of 2,896, participated in the study. Data were collected using a 36-item questionnaire and semi-structured interviews, with motivation assessed based on Deci and Ryan’s (1985) Self-Determination Theory (SDT) and anxiety evaluated using Horwitz’s (1986) framework. Results indicated the following: 1) the students demonstrated moderate levels of motivation; 2) the students exhibited moderate levels of anxiety with communication apprehension emerging as the highest-scoring component of anxiety, and 3) a weak negative correlation suggested a slight inverse relationship between motivation and anxiety, implying that increased motivation might slightly alleviate anxiety. These findings underscore the importance of fostering intrinsic motivation and implementing targeted strategies to mitigate communication apprehension. Although the correlation was statistically significant, its practical significance appears limited, indicating that other factors may play a more substantial role in influencing students' English-speaking anxiety.